Peran Orang Tua dalam Pemahaman Etika Sosial Anak (THUFULA, 2017)
Abstract: THE ROLE OF PARENTS IN THE CHILDREN’S SOCIAL ETHICSUNDERSTANDING. Many parents have difficulty in understanding thebehavior of their children who often seem illogical and incompatible withhealthy feelings. This article tries to describe the roles and approachesparents make in shaping child behavior. To understand children, fosterphysical life, moral development, social development, and personalitydevelopment, parents are required to have knowledge about theirbehavior. Child social development is strongly influenced by the process oftreatment or guidance of parents to children in introducing variousaspects of social life, or norms of community life and encourage and givean example to their children how to apply these norms in everyday life.Parents who want to change their child's behavior first make a change inhim. When parents have successfully adopted a positive approach toencourage children, there will be significant improvements in the behaviorof their children, so that they will develop self-confidence, responsibility,cooperation, and independence in their children.Abstrak: Banyak orang tua mengalami kesulitan dalam memahamiperilaku anak-anaknya yang seringkali terlihat tidak logis dan tidaksesuai dengan perasaan sehat. Artikel ini mencoba mendeskripsikanperan dan pendekatan yang dilakukan orang tua dalam membentukperilaku anak. Untuk memahami anak, membina kehidupan jasmaniah,perkembangan moral, perkembangan sosial, dan perkembangankepribadian, orang tua dituntut memiliki pengetahuan tentang perilakumereka. Perkembangan sosial anak sangat dipengaruhi oleh prosesperlakuan atau bimbingan orang tua terhadap anak dalam mengenalkanberbagai aspek kehidupan sosial, atau norma-norma kehidupanbermasyarakat serta mendorong dan memberikan contoh kepadaanaknya bagaimana menerapkan norma-norma tersebut dalamkehidupan sehari-hari. Orang tua yang ingin mengubah perilaku anaknyapertama-tama melakukan perubahan dalam dirinya. Bilamana orang tuaberhasil menerapkan pendekatan yang bersifat mendorong anak berbuatpositif, pasti akan terjadi perbaikan-perbaikan yang berarti dalamperilaku anak-anaknya, sehingga akan berkembang rasa percaya diri,tanggung jawab, kooperatif, dan kemandirian dalam diri anak-anaknya.